Sort by

- Relevance
- |Time

(

**r**^(2)-36)/((**r**+6)^(2)) The binomial can be factored using the difference...difference of squares formula is a^(2)-b^(2)=(a-b)(a+b). ((**r**-6)(**r**+6))/((**r**+6)^(2)) Reduce the expression by canceling out...5 Answers · Science & Mathematics · 06/03/2010

Assume that

**R**has a divisor of 0, say a different than 0, thus there exists c in**R**...contradiction. If aba = a, then abab = ab thus abab -ab = 0, thus a( bab - b)=0, as**R**has no divisors of 0 we have that bab = b. Take any a...3 Answers · Science & Mathematics · 11/05/2012

**R**(x) = -2x³ - 7x + 14**R**(11) = -2(11)³ - 7(11) + 14**R**(11) = -2(1331) - 77 + 14**R**(11) = -2662 - 77 + 14**R**(11) = -27253 Answers · Science & Mathematics · 03/07/2008

(

**R**(8) -**R**(5)) / (8 - 5) (sqrt(3 * 8 + 1) - sqrt(3 * 5 + 1)) / 3 (sqrt(25) - sqrt(16)) / 3 (5 - 4) / 3 1/31 Answers · Science & Mathematics · 20/01/2017

Simplify: (square the top and bottom of the fraction, then multiply top by

**R**: 22.4 = 14400R/(**R**+139)^2 Clear fraction: (multiply both ...2 Answers · Science & Mathematics · 21/10/2009

(π

**r**^2h)/(2πrh+2π**r**^2)<1/3 (π**r**^2)/(2π**r**+2π**r**^2)<1/3 (π**r**^2)/2π**r**(1+**r**)<1/3**r**/2(1+**r**)<1/3**r**<...2 Answers · Science & Mathematics · 24/08/2012

let

**r**= the radius of the base of the cone , we also have:**R**= radius of sphere**R**+ x = height cone V... - 3x^2 = 0 (**R**+ x)(**R**- 3x) = 0 x = -**R**,**R**/3 => reject the negative root: x =**R**...3 Answers · Science & Mathematics · 26/06/2015

Multiply by

**r**: 1 - 1/2**r**^2 = 3/5**r**1/2**r**^2 + 3/5**r**- 1 = 0 5**r**^2 + 6r - 10 = 0 And solve using the quadratic equation.3 Answers · Science & Mathematics · 05/08/2009

Note that:

**r**^2/(**r**+ 4) => [(**r**^2 - 16) + 16]/(**r**+ 4) = (**r**^2 - 16)/(**r**+ 4) + 16/(**r**+ 4) = [(**r**+ 4)(**r**- 4)]/(**r**+ 4) + 16/(**r**+ 4), by difference of two squares = (**r**- 4) + 16/(**r**+ 4). Thus, the integral becomes: ∫**r**^2/(**r**+ 4) dr...6 Answers · Science & Mathematics · 28/06/2010

Let

**R**be a relation on**R**(all reals) given by x**R**y iff x.... To show**R**is an equivalence relation, then we must show that**R**is reflexive, symmetric, and transitive. Reflexive: We must show...1 Answers · Science & Mathematics · 22/03/2014